SUBJECTIF WELL BEING GURU HONORER DI PONDOK PESANTREN AL MANAR PENGASIH - Imam Mars Miasya; Anas Tri Ridlo Dina Yuliana; Fadhlurrahman Fadhlurrahman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to describe subjective well-being (SWB) honorary teachers at the Al Manar Pengasih Islamic Boarding School, Kulon Progo and to find out the factors that influence the subjective well-being of these honorary teachers. The method used in this research is a qualitative method with a phenomenological approach. The research informants consisted of honorary teachers at the Al Manar Pengasih Kulon Progo Islamic Boarding School, who were selected using a purposive sampling technique. A total of 15 honorary teachers teach at this Islamic boarding school, but the research informants are honorary teachers who teach in the field of Islamic Religious Education, such as jurisprudence, PPKN, and Mathematics, with a teaching period of more than five years. Data collection techniques are carried out through observation, interviews and documentation. The research results show that subjective well-being Honorary teachers at the Al Manar Pengasih Kulon Progo Islamic Boarding School tend to focus on positive cognitive and affective aspects, reflecting satisfaction with their work and the sense of happiness created in carrying out teaching duties.